(untitled) (Journal of Bio-Science, 2011)
Context: Castor is the best candidate plant to the venture of green energy sector. In Bangladesh castor is widely grown and we can reap the benefit from castor by the application of different biotechnological approaches. Genetic engineering appears as one of the necessary tools for the improvement of cultivars of castor. Therefore, an efficient regeneration protocol for castor needs to be established, which is rapid, reproducible and applicable to a broad range of genotypes. Objectives: To establish a high frequency plant regeneration system from the seedling explants of Ricinus communis L. cultivar shabje using tissue culture technique. Materials and Methods: The proliferating axillary shoots were established on modified MS medium supplemented with different concentrations of BA, Kn and 2ip using explants from the in vitro grown seedlings of R. communis. Results: Explants from the seedlings raised on cytokinin enriched medium showed early sprouting and development of axillary shoots than those taken from the seedlings grown on cytokinin omitted medium. Shoot proliferation efficiency of cotyledonary node explant was noted two times greater than that of shoot tip explant. MMS1 medium fortified with 1.5-2.5 mg/l BA showed the best performance and yield 5-10 axillary shoots within 6 weeks of culture. Microcuttings prepared from in vitro proliferated shoots were rooted on MMS2 medium. The best rooting (92.7%) obtained on ½MS fortified with 0.2 mg/l of IBA accompanied by 0.6 mg/l of AgNO3. Conclusion: Best media formulation for shoot proliferation in Ricinus cultivar was MS medium fortified with 2.0 mg/l BA and its recalcitrant property could be minimized in some extent by using of AgNO3 and charcoal in case of root induction. Keywords: In vitro regeneration; seedling explants; Ricinus communis DOI: http://dx.doi.org/10.3329/jbs.v18i0.8787 JBS 2010; 18(0): 121-127